Positive Academic Leadership: Stop Putting Out Fires; Start Making a Difference - Jeff Buller (Academic Chairpersons Conference Proceedings, 2017)
A highly interactive workshop on strategies that can help chairs move towards positive outcomes in even the most negative of situations, making their leadership more effective, effortless, and enjoyable. Participants will come away from this workshop with clear, practical ideas about how they can help their departments become more positive, visionary, and forward-looking.
Keywords: positive academic leadership buller optimism strategies management